Exports to Improve Women's Economic Opportunities in Morocco - Jaime Alfonso Roche Rodriguez; Raymond Robertson; Gladys Lopez-Acevedo; Daniela Ruiz Zárate (Institute of Labor Economics (IZA), 2023)
Morocco's trade liberalization policies coincided with macroeconomic growth over the past two decades. The relationship between trade liberalization and individual-level labor-market outcomes, however, are not well understood. By combining three complementary approaches and modeling techniques, this paper estimates: (i) the relationship between trade agreements and trade flows, (ii) the relationship between trade exposure and various local labor market outcomes, and (iii) the relationship between firm employment and exports. Our results show that tariffs have fallen and trade, as a share of GDP has increased. Morocco's trade agreements, however, are not always associated with higher trade flows. Furthermore, trade has led to mixed results for workers. Increased trade has decreased informality but may have adversely affected female labor force participation (FLFP). Trade liberalization seems to have induced a shift from female labor-intensive industries, such as apparel, to capital-intensive sectors that are predominantly male-intensive. Our firm level analysis confirms these results by showing that increasing in employment from exports has occurred mainly in male, capital-intensive sectors. Labor-abundant countries might want to provide incentives to labor-intensive industries rather than only supporting capital-intensive ones - especially in industries where women typically perform the labor-intensive jobs. It is important to note that we focus mainly on the labor demand side. Policies related to the supply side should also be weighed to create incentives for females to join the labor force, such as policies addressing social norms, regulation, and barriers to job mobility.
Keywords: F13; F14; F15; F16; J23; J31; O15; O19; 330; gender; trade policy; trade flows; labor market outcomes; firm dynamics